Rehabilitation of the athlete's shoulder - Kibler, W. B.; Sciascia, A. (Clinics in Sports Medicine, 2008)
Optimal shoulder function is achieved through segmental activation along the kinetic chain. Alterations within the kinetic chain often contribute to shoulder injury. Therefore, a multi-factorial approach to shoulder rehabilitation, where the causes of shoulder pain as well as site of symptoms, should be implemented.